2017
DOI: 10.18203/2394-6040.ijcmph20171792
|View full text |Cite
|
Sign up to set email alerts
|

To assess the nutritional status among elderly and factors influencing it, in an urban area, Bengaluru - a cross sectional study

Abstract: Background: Elderly population is on raise globally and in India. Malnutrition in old age, significantly increases the susceptibility to infection, compromises the outcomes of other underlying conditions and diseases and hence increases the risk of morbidity and mortality. The malnourished elderly are more likely to require more hospitalizations, cause burden to caregivers and possess a huge economic cost to society. This facilitates the need for early detection of malnourishment among elderly by assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…This could be due to a misunderstanding of the benefits of a well-balanced diet, which aids in the selection, purchase and serving of nutritious meals for better health. The current study supports a previous research report that showed that elderly adults with lower educational status were more likely to be malnourished 38–41…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could be due to a misunderstanding of the benefits of a well-balanced diet, which aids in the selection, purchase and serving of nutritious meals for better health. The current study supports a previous research report that showed that elderly adults with lower educational status were more likely to be malnourished 38–41…”
Section: Discussionsupporting
confidence: 91%
“…Elderly people living in semiurban settings are partially involved in agricultural activities which could support them in providing them with diversified food items, thus help them reduce the risk of malnutrition than urban dwellers. This research is backed up by a global systemic review that found malnutrition is prevalent in socioeconomically disadvantaged urban settings because of accelerating urbanisation, which is accompanied by decreased food access in urban areas emerging from poverty, resulting in poor nutrition and health outcomes 12 39 41–45. The current study discovered that the study subjects were single as their marital status and that they were at a significant risk of malnutrition and being malnourished, which is in agreement with other studies 19 32 42.…”
Section: Discussionsupporting
confidence: 86%
“…This study is in line with the study done in India that found living arrangements without a spouse and children were significantly associated with elderly malnutrition. 29 This may be because of a caregivers' relation to the elder matters more and at this age level, the better caregiver is a related one.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing mainly on socio-economic and demographic status; health care services; common diseases and behavioral characteristics; and anthropometric measurements interviews were carried out by the MNA tool that focused on screening and assessments found in the Nestle Nutrition Institute. Using the MNA score participants are grouped as malnourished (<17), at risk of malnutrition (17-23.5) or normal nutritional status (24)(25)(26)(27)(28)(29)(30) scores. 13 Anthropometric measurements were done by; height measurement, portable height meter was used, and participants measured barefoot, standing in an upright position, with their heel, buttock, shoulder, and prominent occipital against the height meter board.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…As a result, effective geriatric care would necessitate a holistic view of elderly individuals that considers medical, educational, economic, and psychological variables. Malnutrition should be detected early since it is linked to impaired cognitive function, mobility, and the ability to care for oneself [9]. Similarly, to fight geriatric depression, a targeted intervention including nutritional assessment must be emphasized.…”
mentioning
confidence: 99%